Duplications in addition to terminal deletions are present in a proportion of ring chromosomes: clues to the mechanisms of formation. Issue 3 (15th November 2007) - Rossi, E; Riegel, M; Messa, J; Gimelli, S; Maraschio, P; Ciccone, R; Stroppi, M; Riva, P; Perrotta, C S; Mattina, T; Memo, L; Baumer, A; et al.
Abstract : Background and methods: Ring chromosomes are often associated with abnormal phenotypes because of loss of genomic material at one or both ends. In some cases no deletion has been detected and the abnormal phenotype has been attributed to mitotic ring instability. We investigated 33 different ring chromosomes in patients with phenotypic abnormalities by array based comparative genomic hybridisation (CGH) and fluorescence in situ hybridisation (FISH). Results: In seven cases we found not only the expected terminal deletion but also a contiguous duplication. FISH analysis in some of these cases demonstrated that the duplication was inverted. Thus these ring chromosomes derived through a classical inv dup del rearrangement consisting of a deletion and an inverted duplication. Discussion: Inv dup del rearrangements have been reported for several chromosomes, but hardly ever in ring chromosomes. Our findings highlight a new mechanism for the formation of some ring chromosomes and show that inv dup del rearrangements may be stabilised not only through telomere healing and telomere capture but also through circularisation. This type of mechanism must be kept in mind when evaluating possible genotype–phenotype correlations in ring chromosomes since in these cases: (1) the deletion may be larger or smaller than first estimated based on the size of the ring, with a different impact on the phenotype; and (2) the associated duplication will in general cause further phenotypic anomalies and might confuse the genotype–phenotype correlation. Moreover, these findings explain some phenotypic peculiarities which previously were attributed to a wide phenotypic variation or hidden mosaicism related to the instability of the ring.